Answer:
Student B is correct
Student A failed to distribute -4 and -6 when opening the brackets in the first step
Step-by-step explanation:
The solution Student A gave was:
2x - 4(3x + 6) = -6(2x + 1) - 4
2x - 12x + 6 = -12x + 1 - 4
-10x + 6 = -12x - 3
2x = -9
x = -4 _1 2 ( -4 1/2)
The solution Student B gave was:
2x - 4(3x + 6) = -6(2x + 1) - 4
2x - 12x - 24 = -12x - 6 - 4
-10x - 24 = -12x - 10
2x = 14
x = 7
Student B is correct.
Explanation of the error:
Student A failed to distribute -4 and -6 when opening the brackets in the first step.
That is,
2x - 4(3x + 6) = -6(2x + 1) - 4
To open this bracket, we will distribute, -4 and -6 so that we get
2x (-4 × 3x) + (-4 × +6) = (-6×2x) + (-6 × +1) - 4
Then we will get
2x -12x -24 = -12x -6 -4
Adding the like terms
-10x - 24 = -12x - 10
Collecting like terms
-10x + 12x = -10 + 24
∴ 2x = 14
x = 14 / 2
Hence,
x = 7
Answer:
It's a ray because it has a point and one line that goes on in a direction.
Step-by-step explanation:
Answer:
5:3
Step-by-step explanation:
When the ratio says x:y=5:1, it means that x is 5 times greater than y. So, plug in 5 for x and 1 for y.
4(5)+5(1):3(5)
20+5:15
25:15 , if simplified then the ratio 5:3
Because you have not provided an image its hard for me to give you an answer.
Answer:
54, 72, and 90
hope this helps :)
Step-by-step explanation: